WEB-BASED CORRESPONDENCE SERVICE INFORMATION SYSTEM IN DALOM CITY VILLAGE - Danang Kusnadi; Meda Gustiara (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
Kota Dalom is a village in Way Lima District, Pesawaran Regency - Lampung Province. So far, the administrative service system in Kota Dalom village uses services in the form of manual information systems, services carried out by a village official. Some of the problems faced by this server system are difficult and slow in the process. Meanwhile, the community wants friendly, fast, and effective services. So that village officials need a village administrative information system that can help with making letters, recording letters, making KTPs and KKs, as well as a complete reporting feature to facilitate the performance of these village officials. The making of this correspondence system is intended to make it easier for officers and the public to make letters. In terms of efficiency and effectiveness in this system, namely, with this system the work of officers will be more concise, easy, fast to serve and not cause many queues. Making a web-based correspondence information system in the village of Kota Dalom was made to make it easier for users or the public to make letters of good conduct and certificates of domicile. The use of a web-based correspondence information system in Kota Dalom village is carried out by opening the Dalom City village website and then inputting the user's identity. The process of making correspondence in Kota Dalom Village is currently still using a manual system, which means it is still recorded in a ledger. As a result of a system that is still manual, it creates obstacles including the length of the data recording process, lack of employees, delays in letters and poor filing.